RIP VS. OSPF ROUTING PROTOCOLS: WHICH ONE IS THE BEST FOR A REAL-TIME COMPUTER NETWORK? - Majid, Nuur Wachid Abdul; Fuada, Syifaul (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2020)
The development of modern computer networks for internet access makes routing protocols needed, and it has an essential role in a real-time system. Therefore, the best and most effective routes can be reached. In this short article, we discuss the comparison of two popular routing protocols, i.e., Routing Information Protocol (RIP) and Open Shortest Path First (OSPF) using two network simulators, i.e., Graphical Network Simulator-3 (GNS3) and Enterprise Network Simulation Platform (ENSP). Both of OSPF and RIP routing protocols can be used in the same topology and have differences in the connection time required to connect communication between routers. Thru GNS3 and ENSP, we obtained the comparison result at ideal condition; we found that the OSPF routing protocol (83 ms) has a faster time or efficient in connection than RIP (177 ms). Besides, we found that compared to GNS3 network simulators (329 ms), the ENSP has a relatively more rapid average time (94 ms). This work suggests that a Huawei router with ENSP is faster than a Cisco router which is used by GNS3. Hopefully, this information can be refereed by internet network administrators to build real-time computer networks.